2011
DOI: 10.3892/ijo.2011.1066
|View full text |Cite
|
Sign up to set email alerts
|

Rac1b recruits Dishevelled and β-catenin to Wnt target gene promoters independent of Wnt3A stimulation

Abstract: Abstract. We previously reported a functional interaction between aberrant Wnt signaling and Rac1/Rac1b GTPases in tumorigenesis. In this study, we further investigated the mechanistic role of nuclear Rac1b. Using chromatin immunoprecipitation (ChIP) studies, we show that Rac1b resides at the promoters of Wnt target genes, c-Myc and Cyclin D1, in HCT116 cells with aberrant Wnt pathway. In HEK293T cells with intact Wnt signaling, Rac1b is tethered to these same gene promoters independent of Wnt3A stimulation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“… 67 , 68 , 69 In addition, a protein complex composed of RAC1B, β-catenin and disheveled functions to enhance nuclear translocation of transcription factors required for increased interaction with the target promoters. 46 These studies corroborate our proposed mechanism that KRT19 directly interacts with the β-catenin-RAC1 complex to promote nuclear translocation of β-catenin and activate NUMB transcription.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“… 67 , 68 , 69 In addition, a protein complex composed of RAC1B, β-catenin and disheveled functions to enhance nuclear translocation of transcription factors required for increased interaction with the target promoters. 46 These studies corroborate our proposed mechanism that KRT19 directly interacts with the β-catenin-RAC1 complex to promote nuclear translocation of β-catenin and activate NUMB transcription.…”
Section: Discussionsupporting
confidence: 85%
“… 42 , 43 , 44 , 45 Our results revealed that KRT19 knockdown markedly suppressed nuclear translocation of RAC1, a binding partner of β-catenin that aids nuclear translocation of the latter. 43 , 46 Meanwhile, the cytoplasm presented higher amounts of β-catenin and RAC1 in the shKRT19 cells compared with that in control cells.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In agreement, DVL3 but not β-catenin caused increased activation of RAC1B [20]. Follow-up studies have shown that RAC1B resides at the promoters of Wnt target genes, c-Myc and CCND1 , in HCT116 cells with aberrant Wnt pathway [64]. In HEK293T cells with intact Wnt signaling, RAC1B is tied to these same gene promoters independent of WNT3A stimulation and recruits DVL3 and β-catenin in the absence of WNT3A stimulation, suggesting a novel transcriptional coactivator role of RAC1B in β-catenin/TCF-mediated transcription [64].…”
Section: Regulation Of Signaling Pathways By Rac1bmentioning
confidence: 78%
“…Previously, it was demonstrated that Wnt3a does not affect TcdA-induced β-catenin nuclear translocation inhibition ( Lima et al, 2014 ). Because TcdA glucosylates Rho GTPases, such as Rac1 (without affecting Rac1 gene expression in vivo , as shown in Supplementary Figure 1 ), which induces the recruitment of β-catenin to the nucleus ( Wu et al, 2008 ; Pethe et al, 2011 ; Jamieson et al, 2015 ), we investigated whether upregulation of Rac1 through transfection of pcDNA3-EGFP-Rac1-Q61L (as shown in Supplementary Figures 2 , 3 ) could recover Wnt3a-induced β-catenin nuclear translocation in the intestinal epithelial (IEC-6) cells challenged with TcdA. We found that Wnt3a alone induced β-catenin nuclear activity in a manner independent of pcDNA3-EGFP-Rac1-Q61L transfection in the IEC-6 cells, while its transcriptional regulatory response (as demonstrated by the TOPflash/FOPflash, ratio) was inhibited by TcdA with either Wnt3a or Rac1 upregulation alone.…”
Section: Resultsmentioning
confidence: 99%